Analysis of the application for the DFD authoring usage possibilities - Marek Pieczykolan; Marcin Badurowicz (Journal of Computer Sciences Institute)
This article analyzes the possibility of using application to create data flow diagrams, by using QSEE Superlite and the application created in Flutter framework. The purpose of the article is to make comparative analysis of the time needed to create a data flow diagram, as well as to evaluate users in terms of interface transparency and freedom of action in each application. Two research hypotheses have been formulated: “DFD Maker enables faster creation of data flow diagrams compared to QSEE Superlite” and “DFD Maker has a more user-friendly interface compared to QSEE Superlite, allowing for easier creation of data flow diagrams”, which were confirmed after analyzing the results of the conducted study.